2014
DOI: 10.1039/c4cc03740e
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of “rattle-like” polymer particles via suspension polymerization

Abstract: Multiple polymer particles encapsulated in a polymer shell are applied in electrophoretic ink. We demonstrate a simple one-step polymerization of polymer capsules containing small particles (rattle-like particles). In the obtained capsules, encapsulated particles independently dispersed and moved in response to the electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In the TEM image of the CS sample (Fig. ) a salami‐like morphology of the inside of the particles is apparent as expected . As can be seen the spikes have some domains inside that act as a physical barrier against the spike tendency to unite with the parent particle during polymerization, mimicking the effect of crosslinks in previous studies (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In the TEM image of the CS sample (Fig. ) a salami‐like morphology of the inside of the particles is apparent as expected . As can be seen the spikes have some domains inside that act as a physical barrier against the spike tendency to unite with the parent particle during polymerization, mimicking the effect of crosslinks in previous studies (Fig.…”
Section: Resultssupporting
confidence: 79%
“…We recently reported the biggest lobes without crosslinking agent for mace‐like particles . Salami‐like particles have different applications because of their unique internal morphology, but to the best of our knowledge there have been no reports of salami‐like particles with lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that this "Eggshell" was unwashed stabilizer. [28][29][30] Comparing the infrared spectra of gelatin and P(St-DVB) microspheres as in Figure 3A, it could be found that the washed P(St-DVB) microspheres almost have no infrared vibration characteristic absorption peaks of gelatin, which would appear at 1670 cm −1 (OCNH) and 3450-3570 cm −1 (OH and NHR). It indicated that the "Eggshell" was not the unwashed stabilizer gelatin.…”
Section: Surface-wrinkled Microspheresmentioning
confidence: 99%
“…There was a layer of “Eggshell” on the surface of porous microspheres prepared via suspension polymerization. Some studies suggested that this “Eggshell” was unwashed stabilizer . Comparing the infrared spectra of gelatin and P(St‐DVB) microspheres as in Figure A, it could be found that the washed P(St‐DVB) microspheres almost have no infrared vibration characteristic absorption peaks of gelatin, which would appear at 1670 cm −1 (OCNH) and 3450–3570 cm −1 (OH and NHR).…”
mentioning
confidence: 98%
“…We have succeeded in synthesizing rattle-like particles (hollow polymer particles with encapsulated small particles) via a one-step process of suspension polymerization using the self-assembling phase separated polymer method. This was the preparation method proposed by Okubo et al 5) to synthesize hollow polymer particles, wherein ethylene glycol dimethacrylate (EGDM), toluene, and n-hexadecane (HD) droplets dissolve the azobisisobutyronitrile and oil-soluble stabilizer 6) . The obtained capsules had a thin shell and were fully packed with many small particles.…”
mentioning
confidence: 99%